Effect of protein and lipids levels in a growth diet on adult whitebait Galaxias maculatus (Jenyns 1842) - R. Vega-Aguayo; C. Drake; V. Guzmán; A. Mardones; I. Valdebenito; P. De Los Ríos-Escalante; F. Encina-Montoya; J. Barile (Brazilian Journal of Biology, 2021)
Abstract Galaxias maculatus aquaculture objectives is to produce millions of eggs. Wild females are small (2 g), have quick sexual maturity and low mean fecundity (500 eggs/female), requiring larger fishes with higher fecundity. This study aim is to evaluate experimentally the effect of the levels of protein, lipid and dietary energy on weight increases in adults. Five independent experiments were performed at different sequential time periods at the UCT hatchery, Chile. Specimens were obtained from a) Crystalline sea return specimen catches in the Tolten estuary (4 -6 cm, 0.3-0.4 g.). b) Hatchery cultured fish. Fish were fed by hand ad libitum. In experiments 1 to 4, pelleted diets were prepared with 3 to 5 levels of protein (treatments 27 up to 57%), crumble size, three 100 L fibre ponds replicates. In experiment 5 the effect of two lipid levels (8 and 21%) was evaluated with commercial extruded Salmon Nutra Starter isoproteic crumble 1 diet at 63%, replicated in 4 ponds. The results show: A tendency to increased weight in all sizes with an increased protein level in the pelleted diet.A maximal adult growth is obtained with a diet containing a minimum of 37% crude protein, with 40% the optimal value. A higher % protein in the diet or growth in weight lower feed conversion ratio. The feed conversion ratio in the extruded diet reaches up to 0.5 and in the pelleted vary from 0.7 to 1.5. Fish 0.6 g fed with 63% protein, extruded commercial diet with two different lipid levels (8 and 21%, 20.40 and 23.84 MJ kg-1, PE/TE 0.62 and 0.71) increased weight the first month 67 and 105% each. It has been established that high-energy diets with optimal levels of protein and lipid are a good short-term solution to obtain G. maculatus of higher weight.